პლატონი, არისტოტელე და ავგუსტინე რწმენის, ცოდნისა და სიბრძნის შესახებ - ლომაძე, ანა (ლოგოსი, 2022)
The article shows how Plato, Aristotle and Augustine conceive relations between these concepts: belief (faith), knowledge and wisdom. In Plato’s philosophy sometimes belief (δόξα) is contrasted with knowledge (ἐπιστήμη). For him, people who hold true beliefs are like blinds who go the right way. Knowledge is much more valuable, as it’s the only way to grasp eternal and unchangeable things. Knowledge is the highest form of grasping the world for Aristotle too, but he is more optimistic about beliefs. For him endoxa (ἔνδοξα) – the beliefs of the many – are trustworthy and important part of the philosophy. As it regards wisdom (σοφία), both of the philosophers identify this concept with knowledge. Augustine considers that belief (credere) is inseparable from knowledge. When a human knows a thing, she/he also believes in it. Belief, faith (fides) is even wider than knowledge (scientia). Knowledge concerns only changeable things, whereas faith makes it possible to grasp unchangeable things. But grasping them is more perfect, when wisdom (sapientia) helps the faith. A knower can’t grasp unchangeable things, but wise men can make it by contemplating inner truth.